Investigation of amino acids content in the herb and tubers of Stachys sieboldii - Svitlana Marchyshyn; Yuriy Mysula; Vitalii Kishchuk; Liudmyla Slobodianiuk; Elina Parashchuk; Liliia Budniak (Pensoft Publishers, 2022)
The aim of this research was the comparative study of the content of the amino acids in the herb and tubers of Stachys sieboldii. The study of the amino acid composition of the raw materials was carried out using high-performance liquid chromatography (HPLC). The results obtained have shown that the aerial parts of plants investigated have higher amino acid content than the underground organs. Free and bound L-aspartic acid, L-proline, and L-phenylalanine were present in the analyzed samples in the greatest amount. Moreover, L-cysteine was found only in Stachys sieboldii tubers in amounts (8.11 mg/g). This research established that Stachys sieboldii herb and tubers have the most suitable amino acids composition and are prospective for further pharmacological studies.